John Dewey’s Radical Logic: The Function of the Qualitative in Thinking - Pappas, Gregorio Fernando (Análisis. Revista de investigación filosófica, 2022)
In his later works, John Dewey questioned some of the traditional assumptions about the nature and function of the qualitative in inquiry. Dewey foresaw what recent scientific accounts of human thinking are confirming: it is more complex, less linear, more emotional, affective, bodily-based, non-reflective, non-linguistic, non-conscious than philosophers have assumed. Commentators on Dewey have emphasized how inquiry is social, instrumental, and experimental, but for the most part have neglected the qualitative dimension of inquiry. The first section of this essay outlines the different forms that the neglect of the qualitative has taken in Dewey scholarship. The second addresses what Dewey means by the qualitative. The third presents nine specific functions the qualitative has on thinking (inquiry). The essay concludes in the fourth section with some implications of the view presented on the normative dimension of Dewey’s philosophy, and suggests which promising future inquiries remain open regarding the function of the qualitative in inquiry.